Efficient biogas production from cattle manure in a plug flow reactor: A large scale long term study. (April 2019) - Dong, Lili; Cao, Guangli; Guo, Xianzhang; Liu, Tianshu; Wu, Jiwen; Ren, Nanqi
Graphical abstract: Highlights: A large-scale plug flow reactor (PFR) was investigated for biogas production. Efficient and stable biogas production from cattle manure was achieved in PFR. The microbial communities in PFR were explored. A novel approach for producing biogas in large scale from cattle manure was provided. Abstract: In this study, a large-scale plug flow reactor has been operated at a hydraulic retention time of 25 d with substrate concentration of total solids (7–10%) under a temperature of 37–40 °C with a working volume of 3.85 × 10 4 m 3 and dispose 1504 m 3 /d of waste for three years. The average monthly biogas production was 7.45 × 10 4 m 3 . At stable stage, the volume biogas, methane production rate and methane content reached 1.07 m 3 /m 3· d, 0.58 m 3 /m 3· d and 56.4%, respectively. Moreover, the specific biogas and methane yields of substrate removal efficiency were up to 0.39 m 3 /kg VS, 0.22 m 3 /kg VS and 59%, respectively. Among the bacteria, the genera Draconibacteriaceae, Ruminofilibacter, Cloacimonete s and vadinBC27, Ruminiclostridium and Treponema_2 dominated in digestate. The achaeal was dominated by methanogens genera Methanosarcina and Bathyarchaeota . Long-term operation in large scale demonstrated technological potential and industrial application of cattle manure treatment for biogas production.